(untitled) - Ghaus, Farah; Tandon, Rati; Rahman, Nusra; Sharma, Nidhi; Faruqi, Nafis Ahmad (Academia Anatomica International, 2016)
Background: Aminoglycoside antibiotics are still the drug of choice in variable conditions like resistant tuberculosis and septicaemia. Toxic effects are the greatest hurdle in their liberal use. Their central neuro-toxicities specially in terms of affinity are yet to be explored. Methods: Experimental rats received streptomycin, kanamycin and gentamycin in a dose of 30mg/kg, 400mg/kg and 135 mg/kg respectively, IMI, daily for 21 days. Total lipids, phospholipids, cholesterol and gangliosides were estimated in auditory cortex, medial geniculate body, inferior colliculus, cerebellum and spinal cord in both control and experimental rats. Results: On the basis of statistically significant alterations in aforementioned biochemical parameters, affinity of drugs was quantified by scoring. Streptomycin and kanamycin showed maximum toxicity in terms of scoring of 4 with preferential targets i.e. medial geniculate body and inferior colliculus respectively. Gentamycin showed affinity for higher centres only with equal scoring of 3 for toxicity at three locations i.e. auditory cortex, medial geniculate body and inferior colliculus. Conclusion: Such preferential toxicities might reflect some aspects of mechanism of toxicity of different drugs.